A review of scientific topics and literature in abdominal radiology in Germany: Part 1: Gastrointestinal tract = Aktuelle Schwerpunkte und Literatur der Abdominalradiologie im deutschsprachigen Raum : Teil 1: Gastrointestinaltrakt - Schreyer, Andreas; Wessling, J.; Kinner, S.; Juchems, M. S.; Holzapfel, K.; Lauenstein, T. C.; Konietzke, Philip; Grenacher, Lars (RöFo, 2016)
The working group for abdominal and gastrointestinal diagnosis is a group of the German Radiological Society (DRG) focusing clinically and scientifically on the diagnosis and treatment of the gastrointestinal tract with all parenchymatous abdominal organs. In addition to the clinical and scientific further development of abdominal radiology, the education of radiologists within this core discipline of radiology is one of the major aims. In this article we give an up-to-date literature review of scientific radiological topics especially covered by German radiologists. This manuscript focuses on the most recent literature on the diagnosis of the stomach, small bowel, colon and rectum. The review with a focus on the most recent studies published by German radiologists concludes with a synopsis of mesenterial bleeding and ischemia followed by a critical appraisal of the current literature on conventional abdominal radiography.